The Problems of the Independence of Judicial Power in Indonesia in a Review of Islamic Law - Tomi Agustian; Choirul Salim (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, Indonesia, 2021)
Article 24 paragraph 1 of the 1945 Constitution